Goodyera macrantha Maxim-from Kameng District, Arunachal Pradesh - Rao, A. S.; Hajra, P. K. (Indian Forester, 1976)
Goodyera macrantha Maxim, a small ground orchid hitherto known to occur from Japan, is now found at Bomdila in Kameng district of Arunachal Pradesh. The orchid is described, including analytical illustrations.